Strategi Manajemen Program Tahfidz Al-Quran Dalam Meningkatkan Kualitas Hafalan Al-Qur’an Santri Tahfidz Mahad Abu Ubaidah Bin Al-Jarrah - Nisa, Adhlun; Ningsih, Fitria; Ayu, Okta Vira; Pane, Zahrona Romadani (Journal of Sustainable Education, 2025)
This study aims to explore in depth how the management strategies of the Tahfidz Al-Qur’an program are implemented to improve the quality of Qur’an memorization among students at Ma’had Abu Ubaidah bin Al-Jarrah. This research uses a qualitative approach with data collection techniques through in-depth interviews and systematic field observations. The results show that the implementation of structured and sustainable management strategies—including activity planning, selection of appropriate teaching methods, and regular evaluation of memorization—has a significant positive impact on improving students' memorization achievements. In addition, intensive guidance and consistent supervision also play an important role in maintaining the quality of memorization and students’ overall learning motivation.